2021
DOI: 10.1111/nph.17246
|View full text |Cite
|
Sign up to set email alerts
|

Does a trade‐off between growth plasticity and resource conservatism mediate post‐fire shrubland responses to rainfall seasonality?

Abstract: Summary Growth plasticity may allow fire‐prone species to maximize their recovery rates during temporary, sporadic periods of rainfall availability in the post‐fire environment. However, moisture‐driven growth plasticity could be maladaptive in nutrient‐limited environments that require tighter control of growth and resource use. We investigated whether a trade‐off between plasticity and conservatism mediates growth responses to altered rainfall seasonality in neighbouring shrubland communities that occupy d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 75 publications
1
7
0
Order By: Relevance
“…During this phase, the parallel dynamics of Restionaceae, Ericaceae and Proteaceae, which shade and outcompete each other in post-fire fynbos succession (Hoffman et al, 1987;Rutherford et al, 2011) likely reflect a dynamic mosaic pattern at the landscape scale, as is observed at the site today. The expansion of fynbos under enhanced seasonality may suggest the retreat of renosterveld and its replacement by fynbos, in accordance with the findings of van Blerk et al (2021a).…”
Section: Fynbos Development Is Driven By An Increase Of Rainfall Seas...supporting
confidence: 81%
See 2 more Smart Citations
“…During this phase, the parallel dynamics of Restionaceae, Ericaceae and Proteaceae, which shade and outcompete each other in post-fire fynbos succession (Hoffman et al, 1987;Rutherford et al, 2011) likely reflect a dynamic mosaic pattern at the landscape scale, as is observed at the site today. The expansion of fynbos under enhanced seasonality may suggest the retreat of renosterveld and its replacement by fynbos, in accordance with the findings of van Blerk et al (2021a).…”
Section: Fynbos Development Is Driven By An Increase Of Rainfall Seas...supporting
confidence: 81%
“…At the research site, different post-fire responses to manipulated rainfall seasonality had differential impacts on renosterveld and fynbos communities (van Blerk et al, 2021b). Under accentuated summer drought tighter nutrient conservation strategies would afford fynbos taxa a competitive advantage over renosterveld at a community level (van Blerk et al, 2021a). Further mechanisms of post-fire competitive exclusion by seedling shading due to a more frequent fire regime probably explains fynbos resilience over 500 years.…”
Section: Fynbos Development Is Driven By An Increase Of Rainfall Seas...mentioning
confidence: 99%
See 1 more Smart Citation
“…There is a body of work focusing on responses at the molecular level that are related to individual phenotypic plasticity, showing that changes in trait attributes within individuals occur in response to environmental changes (Nicotra et al 2010, Anderson 2016. This is a key point that is not addressed by our analysis but should be considered in future research as it may alter the relative abilities of different species responding positively to climate change where some species benefit from changing their traits (plasticity) (Nicotra et al 2010), and some cannot but benefit from resource conservatism (bet-hedging) (Power et al 2019). Another important consideration for future studies which is gaining momentum in the functional ecology community is that of intraspecific variation in traits.…”
Section: Implications and Future Directionsmentioning
confidence: 86%
“…Moll and Sommerville 1985 ; van der Heyden and Lewis 1989 ) and irrigation during summer has resulted in a 20–40% increase in net photosynthetic rate in one study species (van der Heyden and Lewis 1990 ). Furthermore, recent work has shown limited plasticity in response to experimental changes in seasonal moisture availability in fynbos, particularly in established shrubs (van Blerk et al 2021a , b ).…”
Section: Introductionmentioning
confidence: 99%